The rise and drop of online learning: adaptability and future prospects - Najjar, Najib; Rouphael, Melissa; Bitar, Tania; Hleihel, Walid (Frontiers in Education, 2025)
The landscape of higher education is continuously evolving, with online learning emerging as a prominent educational modality. This cross-sectional study, conducted at the Holy Spirit University of Kaslik (USEK) in Lebanon from January to October 2023, aimed to assess Lebanese students’ perceptions regarding the effectiveness of online learning as a mode of education and to develop strategies and recommendations for enhancing online learning in Lebanon. Using a convenience-sampling method, we collected 309 responses, focusing on educators’ preparedness, student satisfaction, adaptability in online learning, and preferences for future learning modalities. The results highlighted a pressing demand for innovative course design strategies that promote engagement and interactivity, with 41.4% of respondents expressing this need. Additionally, 34.6% of learners emphasized the need for accessible technical support. Furthermore, 38.8% of participants underscored the necessity of comprehensive training programs for educators and learners in navigating online learning environments effectively. Moreover, the preference for online or hybrid learning models (55%) emphasized the importance of flexibility while preserving the value of in-person interactions. The study also highlighted the potential of educational advances to further enhance online learning environments. These technologies could provide opportunities for personalized learning experiences, tailoring course content, delivery methods, and assessments to meet the diverse needs of students, thus fostering a more adaptable and inclusive learning ecosystem. These insights are crucial for refining online education strategies and addressing the evolving needs of students in Lebanon.